SUCCESSFUL CLEARANCE OF CYTOMEGALOVIRUS COLITIS IN ACUTE SEVERE ULCERATIVE COLITIS DURING INDUCTION OF OZANIMOD. (22nd January 2022) - Mohamed, Rana; Kern, Cody; Fein, Aaron; Barrett, Terrence; Perry, Courtney
Abstract: INTRODUCTION: Cytomegalovirus (CMV) colitis, commonly observed in patients with acute severe ulcerative colitis (UC), increases the risk for colectomy and treatment resistance. Unfortunately, corticosteroids and immunomodulators increase CMV reactivation and infection. The use of certain biologics such as anti-TNF mAb increase the risk for CMV colitis, while experience with newer biologics is limited leaving clinicians with few validated options. Ozanimod, an oral sphingosine-1-phosphate receptor modulator, was recently approved for induction and maintenance therapy for UC. Experience with ozanimod in the setting of UC complicated by CMV infection has not been reported to this date. We report here on a severe UC patient with tissue proven CMV ulceration that cleared the viral infection during ozanimod induction. CASE REPORT: A 21-year-old male with UC treated with tofacitinib presented with five days of diffuse abdominal pain and 10-12 episodes of bloody diarrhea per day with CRP 341mg/L (<8.0mg/L) and calprotectin >3000μg/g (<49μg/g). Computed topography of the abdomen and pelvis showed diffuse wall thickening and mucosal enhancement throughout the entire colon and rectum. He was started on methylprednisolone 20mg TID for acute severe UC. He previously failed infliximab, adalimumab, ustekinumab, and vedolizumab. Colonoscopy showed pancolitis (Mayo score 3) with deep ulceration in the cecum. Random colon biopsies were consistent with active colitis with an area of CMV infection in an area of cecal ulceration (Figure 1). Serum CMV Quantitative PCR was 410IU/ml (normal <50IU/ml). The patient refused colectomy and was started on IV ganciclovir 5mg/kg q12h while transitioning to prednisone 40mg/day. Three weeks after initial presentation and eleven days after starting ganciclovir, the patient began ozanimod. He remained on ganciclovir for three weeks then transitioned to oral valganciclovir 900mg BID. The patient's symptoms improved, CRP normalized, and calprotectin levels dropped (1200μg/g). Repeat colonoscopy performed eighteen days after ozanimod initiation revealed moderately-improved pancolitis (Mayo 2) with multiple healing cecal ulcers. Analysis of cecal ulceration IHC and peripheral blood PCR indicated clearing of the infection from the colon (Figure 2). DISCUSSION: Cytomegalovirus colitis remains a common complication in severe UC, while avoidance of colectomy with viral clearance remains a challenge. Ozanimod and ganciclovir were chosen by this patient after refusing surgical resection. The improvement in clinical biomarkers of colitis and viral clearance suggest that ozanimod given with ganciclovir may be an exciting rescue therapy in these patients. Future studies will be needed to ascertain the rates of ozanimod response and CMV clearance in a larger patient cohort.